Association of nutritional status and mortality risk in patients with primary pulmonary hypertension. (12th January 2022) - Luo, Dongling; Xie, Nanshan; Yang, Ziyang; Zhang, Caojin
Abstract: Malnutrition plays a crucial role in pulmonary hypertension (PH). The prognostic nutritional index (PNI) is a reliable indicator for nutritional status assessment. However, its relationship with mortality risk in PH patients has not yet been investigated. This study analyzed data from the Patient Registry for Primary PH. PNI was calculated through albumin and lymphocyte counts. Subjects with missing data for PNI calculation were excluded. The primary endpoint was all‐cause mortality. Cox proportional hazard model was used to calculate the hazard ratios (HRs) and 95% confidence intervals (CIs). Of the 317 patients records available in the registry, we finally included 136 patients. The average age of the included subjects was 40.56 (14.91) years and 63.24% (86/136) were female. In our analysis of Cox regression, per 1‐point increment of PNI was associated with 4% decreased risk of mortality in PH patients (age‐ and sex‐adjusted HR: 0.96, 95% CI: 0.93–0.98, p  = 0.002). We further categorized these subjects by quartiles of PNI. Compared to quartile 4, the age‐ and sex‐adjusted HRs of death for quartiles 1, 2, and 3 were 2.39 (95% CI: 1.21–4.72, p  = 0.01), 2.25 (95% CI: 1.15–4.39, p  = 0.02), and 1.72 (95% CI: 0.84–3.52, p  = 0.14). In addition, logistic regression analyses suggested a positive correlation of PNI with total lung capacity ( β  = 0.98, p  = 0.002) and forced expiratory volume in 1 min ( β  = 1.53, p  = 0.03). This study demonstrates that low PNI was associated with an increased risk of death in PH patients. These findings help to enlighten our understanding of the nutritional status and adverse outcomes in PH patients.